2021
DOI: 10.1051/0004-6361/202040070
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering erosion effects on magnetic flux rope twist

Abstract: Context. Magnetic clouds (MCs) are transient structures containing large-scale magnetic flux ropes from solar eruptions. The twist of magnetic field lines around the rope axis reveals information about flux rope formation processes and geoeffectivity. During propagation MC flux ropes may erode via reconnection with the ambient solar wind. Any erosion reduces the magnetic flux and helicity of the ropes, and changes their cross-sectional twist profiles. Aims. This study relates twist profiles in MC flux ropes ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Magnetic erosion affects ∼30% of the ICMEs at 1 au, and it can be most reliably identified from the presence of reconnection exhausts and bifurcated current sheets near FR boundaries (Ruffenach et al 2015). Erosion also implies large-scale magnetic field topological changes occurring within ICMEs (Ruffenach et al 2012;Pal et al 2021), and yet, the full breadth of effects on magnetic field configurations within MEs and FRs therein remains unclear. In the following, we investigate the relationship between ME and FR duration as a potential proxy for magnetic erosion.…”
Section: Fr-to-me Duration Scaling With Heliocentric Distancementioning
confidence: 99%
“…Magnetic erosion affects ∼30% of the ICMEs at 1 au, and it can be most reliably identified from the presence of reconnection exhausts and bifurcated current sheets near FR boundaries (Ruffenach et al 2015). Erosion also implies large-scale magnetic field topological changes occurring within ICMEs (Ruffenach et al 2012;Pal et al 2021), and yet, the full breadth of effects on magnetic field configurations within MEs and FRs therein remains unclear. In the following, we investigate the relationship between ME and FR duration as a potential proxy for magnetic erosion.…”
Section: Fr-to-me Duration Scaling With Heliocentric Distancementioning
confidence: 99%
“…It exhibits a tail-like structure after around June 26 02:00 UT where the field components remain essentially constant. This is often interpreted as a sign of flux-rope erosion by magnetic reconnection with the ambient wind (e.g., Dasso et al 2007;Pal et al 2021).…”
Section: June 23 Cmementioning
confidence: 99%
“…Moreover, the percentage of eroded magnetic flux is very case dependent and so this needs to be taken into account in MC studies. In particular, from the analysis of two studiedcases, Pal et al (2021) concluded that the erosion has significant effects on the obtained magnetic flux rope twist, as it is expected mainly due to the lack of its external part, which typically is highly twisted.…”
Section: Introductionmentioning
confidence: 99%